3(x+y)=y
y is not equal to zero
*Solution
1. The given equation is 3(x+y) = y and we are tasked to find the ratio between x and y. Distributing 3 to the terms in the parenthesis,
3(x+y) = y
3x + 3y = y
Transposing 3y to the right side OR subtracting 3y from both the left-hand side and the right-hand side of the equation would give
3x = -2y
Dividing both sides of the equation by 3,
x = (-2/3)y
Dividing both sides of the equation by y,
x/y = -2/3
Therefore, the ratio x/y has a value of -2/3 provided that y is not equal to zero.
You would multiply 6.2 by -4 which is -24.8 so then the equation is y+-24.8=-13 then add -24.8 to both sides and it will be y=11.8
JK where T is the midpoint. J >>>>> T >>>>> K.
JK = 5x - 3
JT = 2x + 1
Because T is the midpoint, it means that JT = TK
So, JT + TK = JK
(2x + 1) + (2x + 1) = 5x - 3
4x + 2 = 5x - 3
4x - 5x = -3 - 2
-x = -5
x = 5
JK = 5x - 3
JK = 5(5) - 3
JK = 25 -3
JK = 22
The length of JK is 22.
Perimeter = 2w + 2l = 2(12) + 2(10) = 44